Whistleblowing on Anti-Competitive Conduct under the Trade Secrets Directive and the Finnish Trade Secrets Act - Zimmermann, Sophie (My University, 2018)
In 2016, the European Union adopted a directive for the protection of trade secrets against their misappropriation. In addition to mending the patched trade secrets legislation within the EU, the directive included exceptions to trade secret protection. According to one exception, trade secret disclosure is allowed in the event that it is done for the purposes of whistleblowing. Subsequently, the provision has become an important part of whistleblowing discussion as whistleblowing legislation is also patched in the EU. This whistleblower exception is notably broad in its terminology and scarce in any transposition guidelines. Therefore, when it was transposed on a national level in the summer of 2018, the Finnish legislator made some specifications in the government proposal which were not derivative from the wording of the Trade Secrets Directive. These specifications have especially been criticized by the Finnish competition authority due to the claimed chilling effect they would have on individual whistleblowing on anti-competitive conduct. Using the legal dogmatic method, this research firstly introduces and assesses the ambiguities in the Trade Secrets Directive, secondly assesses the specifications made by the Finnish legislator and finally researches their effects on the reporting and investigation of anti-competitive conduct. In order to assess these matters, this research draws information from the fundamentals of EU law and its transposition to national level in addition to the findings and alignments made on international whistleblowing and whistleblowing in the realm of competition law. The conclusions made in this research are that the broadness of the Trade Secrets Directive has led to the Finnish legislator using other source material besides the directive when specifying the whistleblower exception in the national legislation. It can also be argued that the Finnish legislator has taken the specifications too far from the realm of the directive. Additionally, the stances taken by many operators underline the inherent opposing interests at hand when discussing whistleblowing. In order to satisfy all these interests to the furthest extent, a tiered approach to whistleblowing is the optimal choice, although not one to entirely erase the opposing views.
Keywords: European Union, Trade Secrets Directive, Finnish Trade Secrets Act, terminological vagueness, transposition, implementation, whistleblowing, competition authority, competition policy, anti-competitive conduct, balance of interests